THERMO-DIFFUSION AND DIFFUSION-THERMO EFFECTS ON MIXED CONVECTION HYDROMAGNETIC FLOW IN A THIRD GRADE FLUID OVER A STRETCHING SURFACE IN A DARCYFORCHHEIMER POROUS MEDIUM (FUDMA JOURNAL OF SCIENCES, 2023)
This paper is concerned with the influences of thermo-diffusion and diffusion-thermo on the mixed convection flow, heat and mass transfer of a viscoelastic third grade fluid along a vertical surface in a Darcy- Forchheimer porous medium. The surface is assumed to be permeable in the presence of thermal radiation, Joule heating, viscous dissipation, non-uniform heat source/sink and chemical reaction of order n . Adopting the equation for conservation of momentum for the third grade fluid, the basic boundary layer equations of heat and mass transfer, which are nonlinear partial differential equations, are converted into a system ofcoupled nonlinear ordinary differential equations by means of similarity transformations. Numerical solutions are obtained for the resulting boundary value problems by employing midpoint integration scheme enhanced by Richardson’s extrapolation. The effects of various pertinent parameters are shown in several plots. Skinfriction coefficient, local Nusselt and Sherwood numbers are tabulated in order to gain more insight into the surface shear stress, rates of heat and mass transfer of the problem. Soret and Dufour numbers are found to be increasing functions of the species concentration and thermal boundary layer thicknesses respectively.
Keywords: Mixed convection, Thermo-diffusion, Diffusion-thermo, Hydromagnetic flow, Third grade fluid